1997
DOI: 10.1046/j.1464-410x.1997.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Is obstruction predictable by clinical evaluation in patients with lower urinary tract symptoms?

Abstract: Objective To determine whether it is possible to predict correlation for the IPSS and the quality-of-life question of the IPSS. The percentage of patients with BOO the presence of bladder outlet obstruction (BOO) by non-invasive clinical variables in patients with lower defined by a linPURR of 3-6 decreased from 85% in those with a Q max of 0-5 mL/s to 60% (Q max urinary tract symptoms (LUTS) suggestive of BOO. Patients and methods Patients with LUTS suggestive of 6-10 mL/s) and 44% (Q max 11-15 mL/s). In para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
2
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 5 publications
4
37
2
1
Order By: Relevance
“…Most community-based studies showed that age and symptom scores showed a positive correlation (16)(17)(18)(19)(20) as well as an increase in LUTS severity with age. Despite some studies showing a negative correlation between age and symptom indexes (11,21), the majority of the studies including ours showed an increase in symptom scores with age. Patients often complaint about more severe symptoms as their daily-life activities are disrupted and consequently, their quality of life is reduced (22,23).…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Most community-based studies showed that age and symptom scores showed a positive correlation (16)(17)(18)(19)(20) as well as an increase in LUTS severity with age. Despite some studies showing a negative correlation between age and symptom indexes (11,21), the majority of the studies including ours showed an increase in symptom scores with age. Patients often complaint about more severe symptoms as their daily-life activities are disrupted and consequently, their quality of life is reduced (22,23).…”
Section: Discussioncontrasting
confidence: 89%
“…Moreover, we also found statistically significant correlations with increased post-void residue with the severity of symptoms in IPSS questionnaire. Likewise, another study in the literature showed a significant relationship between IPSS and post-void residue (11). When IPSS scores and prostate volume and PSA were compared, we detected a significant correlation between those parameters.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Uroflowmetry was assessed in 2580 patients across 16 studies. Thirteen studies used a cutoff value of 10 ml/s to diagnose BOO and reported median sensitivity of 68.3%, specificity of 70.5%, a PPV of 74.3% and NPV of 68% [7,12,13,15,16,18,20,21,26,30,33,34,38,40,41]. However, studies varied considerably in their choice of defining variable and cutoff values.…”
Section: Diagnostic Accuracy Resultsmentioning
confidence: 99%
“…La hipertrofia vesical es una consecuencia de la obstrucción infravesical y produce un incremento en el volumen de la pared vesical (13). Así lo confirman hallazgos de la reducción del grosor de la pared vesical después de la resolución quirúrgica de la obstrucción (14).…”
Section: Discussionunclassified